2016
DOI: 10.1371/journal.pone.0154600
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Niches of Two Invasive Genotypes of the Wheat Curl Mite Aceria tosichella: Congruence between Physiological and Geographical Distribution Data

Abstract: The wheat curl mite (WCM), Aceria tosichella Keifer, is a major pest of cereals worldwide. It is also a complex of well-defined genetic lineages with divergent physiological traits, which has not been accounted for in applied contexts. The aims of the study were to model the thermal niches of the two most pestiferous WCM lineages, designated MT-1 and MT-8, and to assess the extent to which temperature determines the distribution of these lineages. WCM population dynamics were modeled based on thermal niche dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

7
0

Authors

Journals

citations
Cited by 17 publications
(35 citation statements)
references
References 61 publications
2
33
0
Order By: Relevance
“…Indeed, the population density patterns of MT-1, MT-8 and additionally MT-3 (which also sporadically infest cereals) suggest that these lineages fare poorly in cold regions (see Figs 2D, 3D and 4D), including the north central (Gulf of Gdańsk) and northeastern regions and southern mountain ranges. This pattern is consistent with a recent study that modeled the most thermally suitable areas in Poland for population development of MT-1 and MT-8, which showed that the majority of Poland offers optimal thermal conditions for growth of both lineages from May to September [32]. …”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Indeed, the population density patterns of MT-1, MT-8 and additionally MT-3 (which also sporadically infest cereals) suggest that these lineages fare poorly in cold regions (see Figs 2D, 3D and 4D), including the north central (Gulf of Gdańsk) and northeastern regions and southern mountain ranges. This pattern is consistent with a recent study that modeled the most thermally suitable areas in Poland for population development of MT-1 and MT-8, which showed that the majority of Poland offers optimal thermal conditions for growth of both lineages from May to September [32]. …”
Section: Discussionsupporting
confidence: 92%
“…MT-1 and MT-8), due to their pest and invasion potential and acceptance of multiple grass species as hosts [25], are widely distributed and abundant across the whole area of Poland. This assumption is additionally supported by previous studies showing that the majority of Poland offers optimal thermal conditions for the development of both lineages [32]. Third, we hypothesized that genetic lineages within the WCM complex avoid competition through the partitioning of resources in terms of host species or spatial distribution.…”
Section: Introductionsupporting
confidence: 56%
See 2 more Smart Citations
“…Apart from green bridges, climate and weather conditions may influence the levels of WCM infestation and WSMV infection. It has been suggested that high temperatures are the most preferable for MT‐1 and MT‐8 WCM lineages (Kuczyński et al ., ). According to Orlob (), dry and hot conditions favour the development of WCM populations.…”
Section: Virus Transmission By Wcmmentioning
confidence: 97%